Answer: month 4
Explanation
ill try to explain this as simple and short as possible
our equations are
f(x) = 3x and g(x) = 7x + 6
we need to see which one grows faster per month. so all you do is plug in the number of months into X in each equation then solve. once you have an answer, plug in the next number of months til you have an answer
we already have the first and second months of each equation so now you just do the next four
for f(x) the growth per month is this
1 month = 3
2 months =9
3 months =27
4 months =81
5 months = 243
and 6 = 729
good, next we for g(x) we plug in the number of months and we get
1 month= 13
2 month = 20
3= 27
4= 34
5= 41
6= 48
SO f(x) starts growing exponentially faster than g(x) during the 4th month, because that's when it starts increasing faster
hope this wasn't too complex, sorry its so long